Recent progress of ultra-narrow-bandgap polymer donors for NIR-absorbing organic solar cells. Issue 15 (1st July 2021) - Lim, Dae-Hee; Ha, Jong-Woon; Choi, Hyosung; Yoon, Sung Cheol; Lee, Bo Ram; Ko, Seo-Jin
Abstract : This review provides a comprehensive understanding of the chemical structure and overall development trend for solution-processable NIR-absorbing ultra-narrow-bandgap (UNBG; below 1.5 eV) polymer donors used in organic solar cells. Abstract : Solution-processed near-infrared (NIR)-absorbing organic solar cells (OSCs) have been explored worldwide because of their potential as donor:acceptor bulk heterojunction (BHJ) blends. In addition, NIR-absorbing OSCs have attracted attention as high specialty equipment in next-generation optoelectronic devices, such as semitransparent solar cells and NIR photodetectors, owing to their feasibility for real-time commercial application in industry. With the introduction of NIR-absorbing non-fullerene acceptors (NFAs), the value of OSCs has been increasing while organic donor materials capable of absorbing light in the NIR region have not been actively studied yet compared to NIR-absorbing acceptor materials. Therefore, we present an overall understanding of NIR donors.